Inclusive Waldorf schools today: what can we build on and what is necessary in the 21st century? - Barth, Ulrike; Wiehl, Angelika (Frontiers in Education, 2024)
In this article we deal with questions of inclusion or inclusive educational requirements in schools and pay special attention to Waldorf schools. In doing so, we are first concerned with the question of how inclusive Waldorf education is in its foundations in order to then look more closely at the situation in Waldorf schools today and explore what potential Waldorf education has. A contribution to this is the research we are doing on the methodology of perception vignettes. For four years we have been using this methodology to develop an approach of “understanding” diagnostics for our students and future Waldorf teachers, so that they can consult different perspectives in their everyday dealings with children and adolescents and learn to ask the appropriate questions.